Chronic myeloid leukemia presenting in lymphoblastic crisis, a differential diagnosis with Philadelphia-positive B-lymphoblastic leukemia. Issue 12 (14th October 2020) - Chen, Zhining; Hu, Shimin; Wang, Sa A.; Konopleva, Marina; Tang, Zhenya; Xu, Jie; Li, Shaoying; Toruner, Gokce; Thakral, Beenu; Medeiros, L. Jeffrey; Tang, Guilin
Abstract: Rare patients with chronic myeloid leukemia (CML) can present initially in lymphoblastic crisis (LBC) mimicking Ph + B-lymphoblastic leukemia (B-ALL). We retrospectively reviewed 275 adults who diagnosed initially as Ph + B-ALL and identified 28 patients with at least one of three features supporting the diagnosis of CML-LBC: 1) a large discrepancy between the blast count and Ph + clone; 2) Ph + clone persistent when B-ALL in remission; 3) BCR/ABL1 fusion detected in segmented cells. BCR-ABL1 fusions were p210 in 25 patients and p190 in 3 patients. In comparison to patients with Ph + B-ALL, patients with CML-LBC were older; had higher leukocyte and absolute neutrophil counts; higher immature myeloid cells in peripheral blood; lower blast counts; and inferior outcomes. In addition, we prospectively analyzed 26 patients with Ph + B-lymphoblastic leukemia and identified 8 patients with features more consistent with CML-LBC. These findings highlight the importance of distinguishing CML-LBC from de novo Ph + B-ALL.